-4m+4=-59+3m

Simple and best practice solution for -4m+4=-59+3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4m+4=-59+3m equation:


m in (-oo:+oo)

4-4*m = 3*m-59 // - 3*m-59

4-4*m-(3*m)+59 = 0

4-4*m-3*m+59 = 0

63-7*m = 0 // - 63

-7*m = -63 // : -7

m = -63/(-7)

m = 9

m = 9

See similar equations:

| -6d+4=4d-96 | | 5/6x-1/5x+4+7/10x | | 3s^2-5s+2= | | -7d-6=-6+3d | | 6x+7=-2x-33 | | 1+2d=6d+49 | | 2y+x=2y-8 | | 3x-7=56-6x | | -9-4d=d-29 | | -7b+4=-b-68 | | x-10=-7x+46 | | 7d+1=4d+34 | | -6-5x=-x-30 | | -1+x=-4x-56 | | 3a-4=68-6a | | -5-k=6k-40 | | c+54=6 | | -2d-9=-27+4d | | 3b-10=-b-6 | | 2t-1=-25-2t | | 5-3w=-5w-19 | | 2n+7=3n+9 | | y=-6+21 | | -6+7a=3a-54 | | 2m-5=3m-12 | | b+8=7b+32 | | -4+w=4w-37 | | x^2-9x-190=0 | | 6y^2-5y-1= | | 3+12s-1=5s+92-3s | | 2(x+3)-3(2x-9)= | | 10n-6=9n+2 |

Equations solver categories